Influencia del programa de educación sexual habla serio sexualidad sin misterios impartido en adolescentes de la ciudad de Zamora, en relación a la prevención de embarazos. - Díaz Yaguachi, Fabricio Miguel (2014)
This present study, named influence of sex education program serious talk sexuality without mysteries given to teenager in Zamora city to prevent pregnancies, it is a descriptive study of transversal cohort its objectives are: determine the influence of the program in pregnancy prevention, determine the numbers of teenagers who were trained on sexuality, establish the contraceptive method the most used by teenagers, establish the incidence of pregnancy teenagers before and after to apply the program in the period 2011- 2014. This agreement was performed in the implementation program serious talk sexuality without mysteries with teenagers in this city, in July 2012 to September 2014, in this study was applied the data collection with the following results: teenagers trained in the program mainly are men, in 2012 was 55, 29 % men and 44, 71 % women. During 2013 56, 50 % were men and 43, 50 % were women, in 2014 are been trained, 56, 03 % men and 43, 97 % women. The age group more trained were 15-19 years old, in 2012 were 76,00 % , for 2013 was 58,33 % , but in 2014 the highest age group is 10-14 years old with the 64,21 %. The most frequently used contraceptives were the male condoms: 2012 (59, 33 %), 2013 (79, 91 %), 2014 (59,87 %). Among condom dispensers, the most frequently used contraceptives were the male condom: 2012 (87, 57 %), 2013 (92, 03 %), 2014 (87,51 %). The frequency teenage pregnancy before the program (2011) was of 84 by each 1000 teenager’s women; when start the program sex education (2012) until the present date (2014) the frequency of pregnancies in teenagers has been reduced to 20 by each 1000 teenager women. Emphasizing the positive influence of this program reduce teenage pregnancy. Keywords: teenage pregnancy, program serious talk sexuality without mysteries